Geht es in der GKV gerecht zu? Zur Kritik am Morbi-RSA - Thomas Neusius (RheinMain University of Applied Sciences, Wiesbaden Institute of Finance and Insurance (wifi), 2017)
Der Morbi-RSA ist ein zentrales Element um einen fairen Wettbewerb der gesetzlichen Krankenkassen untereinander zu ermöglichen. Zuletzt nahm jedoch die Kritik am Verfahren zu. Hier wird ein Überblick über die aktuellen Streitpunkte und ihre wissenschaftliche Absicherung durch verschiedene Gutachten gegeben. – – The Morbi-RSA (morbidity-based risk structure compensation) is central for allowing a fair competition among the german statutory health insurance companies. Recently, substantial critic has been uttered. We give an overview over various points of discussion and the evidence provided by a number of recent expertises.
Keywords: I13; 330; Wettbewerb; Risikostrukturausgleich; Gesetzliche Krankenkasse